Synthesis, optical and electrical characterization of amino-alcohol based sol-gel hybrid materials - Gomes, Bárbara R. (2020)
This manuscript describes the synthesis and characterization of five new organic–inorganic hybrid (OIH) sol-gel materials that were obtained from a functionalized siloxane 3-glycidoxypropyltrimethoxysilane (GPTMS) by the reaction with the new Jeffamine®, namely three different diamines, i.e., EDR-148, RFD-270, and THF-170, a secondary diamine, i.e., SD-2001, and a triamine, i.e., T-403. The OIH sol-gel materials were characterized by UV-visible absorption spectrophotometry, steady-state photoluminescence spectroscopy, and electrochemical impedance spectroscopy. The reported OIH sol-gel materials showed that, with the exception of the samples prepared with Jeffamine® SD-2001, the transmittance values ranged between 61% and 79%. Regarding the capacitance data, the values reported changed between 0.008 and 0.013 nF cm−2. Due to their optical and electrical properties these new OIH materials show promising properties for applications as support films in an optical sensor area such as fiber sensor devices. Studies to assess the chemical stability of the OIH materials in contact with cement pastes after 7, 14, and 28 days were also performed. The samples prepared with THF–170 and GPTMS, when compared to the samples prepared with RFD-270 and T-403, exhibited improved behavior in the cement paste (alkaline environment), showing promising properties for application as support film in optical fiber sensors in the civil engineering field.